A Analisis Gaya Belajar Visual, Auditori, dan Kinestetik (VAK) pada Pembelajaran Biologi Siswa SMAN 8 Bulukumba - Azis, Suhartini; Andi Yurni Ulfa; Akbar, Fauzan; Haerul Mutiah; Halijah (Universitas Islam Jember, 2022)
Learning style is a way or habit of learning among students that supports learning objectives so that it has an impact on improving learning outcomes. Each student has a different learning style; there are visual, auditory, kinesthetic or a combination of these learning styles. This study aims to determine the visual, auditory, kinesthetic and combined learning styles of the students of class X MIPA SMAN 8 Bulukumba in learning biology. The type of research used is descriptive quantitative, with research subjects as many as 178 people who were distributed in 5 classes in parallel using a questionnaire instrument. The data analysis technique in this research is descriptive quantitatively through the percentage of students' learning style tendencies. Based on the results of the research on the trend of learning styles in parallel where students of class X MIPA1 tend to have an auditory learning style by 31.43%, X MIPA2 tends to a visual style 33.33%, X MIPA3 tends to a visual style 36.11%, X MIPA4 tends to an auditory style by 33.33%, and X MIPA5 tends to be a visual style of 43.14%. Overall, the learning styles of Class X Mathematics and Natural Sciences students tend to be visual learning styles by 30.9% or about 55 people, and the lowest in the combined auditory-kinesthetic style by 6.74% or about 12 people. The conclusion of this research is that students in class X MIPA in biology learning at SMAN Bulukumba have the highest tendency to learn style in visual style.